Analysis Of Irrigation Development In Economic Welfare Of Farmers In Tanjung Keriahan Village Langkat Regency - M Ryansyah; Muhammad Yafiz (Penerbit Jurnal Indonesia, 2022)
The agricultural sector is the main sector for the economy of most developing countries, including Indonesia. During the Covid-19 pandemic, the agricultural sector remained the mainstay sector, because it was able to survive during the pandemic, while many other sectors experienced setbacks. And infrastructure plays an important role in driving the wheels of economic growth and development. The purpose of this study was to determine how the impact of the construction of irrigation networks on the welfare of farmers. The research method used is desk study. This research data uses secondary data sourced from books, journals, articles and the internet. The results showed that the construction of irrigation networks was very beneficial for farmers. Because it can increase the intensity of planting in the fields. Increasing cropping intensity in paddy fields will have implications for increasing farmer productivity. So that it is expected to increase the income of rice farmers which in turn will be able to improve welfare.